2021
DOI: 10.3390/catal11040522
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Particles Modified by Mixed-Frequency Square-Wave Potential Treatment to Enhance Electrocatalytic Performance for Formic Acid Oxidation

Abstract: Palladium catalysts have attracted widespread attention as advanced electrocatalysts for the formic acid oxidation (FAO) due to their excellent electrocatalytic activity and relatively high abundance. At present, electrodeposition methods have been widely developed to prepare small-sized and highly-dispersed Pd electrocatalysts. However, the customary use of surfactants would introduce heterogeneous impurities, which requires complicated removal processes. In this work, we reported a two-step electrochemical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Subsequently, a slow decay of the current density was observed, which was associated with surface poisoning by intermediates [7]. The current density of the Pd-Pt bimetallic catalysts with a dendritic morphology for a period of 3000 s was 0.08 A mg −1 , which was higher than those of PdPts-10 Hz (0.04 A mg −1 ), PdPts-90 Hz (0.04 A mg −1 ), PdPts-1 H (0.02 A mg −1 ), and PdPts-2 H (0.03 A mg −1 ), even four times that of the commercial Pd/C catalyst reported in the literature (about 0.02 A mg −1 ) [36]. This indicated that the Pd-Pt bimetallic catalysts with a dendritic morphology possessed an outstanding catalytic activity and a high stability towards FAOR in an acid medium.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Subsequently, a slow decay of the current density was observed, which was associated with surface poisoning by intermediates [7]. The current density of the Pd-Pt bimetallic catalysts with a dendritic morphology for a period of 3000 s was 0.08 A mg −1 , which was higher than those of PdPts-10 Hz (0.04 A mg −1 ), PdPts-90 Hz (0.04 A mg −1 ), PdPts-1 H (0.02 A mg −1 ), and PdPts-2 H (0.03 A mg −1 ), even four times that of the commercial Pd/C catalyst reported in the literature (about 0.02 A mg −1 ) [36]. This indicated that the Pd-Pt bimetallic catalysts with a dendritic morphology possessed an outstanding catalytic activity and a high stability towards FAOR in an acid medium.…”
Section: Resultsmentioning
confidence: 53%
“…Two well-defined current peaks P1 and P2 appeared at about 0.44 V (vs. SCE) and 0.78 V (vs. SCE) (Figure 6a), corresponding to the direct oxidation of formic acid to CO2 and oxidation of adsorbed CO generated by dehydration of formic acid, respectively [7,14]. The Pd-Pt bimetallic catalysts with a dendritic morphology (PdPt-50 Hz (4 H)) exhibited the highest mass activity (P1, 0.77 A mg -1 ) among the obtained Pd-Pt bimetallic catalysts towards FAOR and was almost 2.5 times that of the commercial Pd/C catalyst (0.31 A mg -1 ) [36]. Furthermore, the Pd-Pt bimetallic catalysts with a dendritic morphology also displayed a higher mass activity compared with the reported Pd-based electrocatalysts towards FAOR (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation